PROTEIN ENERGY ADEQUACY LEVELS ON PHYSICAL FITNESS IN BADMINTON PLAYERS AT IKBIS SURABAYA - Ahmad Hariyanto; Bambang Gunawan; Nurul Hidayati (International Journal of Social Science, 2024)
Badminton is a sport that uses a combination of strength and endurance. Badminton athletes need to have good physical fitness to produce oxygen for energy formation. Factors that influence physical fitness are age, gender, genetics, nutritional status, nutritional intake, and physical activity. The research aims to determine the level of protein intake of badminton players on the physical fitness of students at Ikbis Surabaya. The research was carried out at the IKBiS Surabaya Badminton Court using descriptive analytical methods. The research sample was 11 respondents who were badminton players at the Surabaya Health and Business Institute who were registered with the Surabaya Health and Business Institute UKM. Research data includes the level of nutritional adequacy and physical fitness of badminton players at the Surabaya Institute of Health and Business. The research results showed that the majority of respondents had a good level of protein adequacy of 54.5%. At the level of physical fitness, male and female athletes have a very poor category of 60.0% and 83.35%. It was concluded that there was a relationship between Protein Energy Adequacy Level and Physical Fitness among students at IKBIS Surabaya